Assessing the Therapeutic Potential of Arctium lappa L. (Burdock Root) Ethanol Extract in Wound Healing on Male Rattus norvegicus - Imam Faizal; Jodi Irmansa; Ira Pangesti; Frinsisca Oktaviany; Aprillia Avivah Ledyana Mas’ud; Dilla Putri Oktafiani; Silviana Dwi Yuniasari (Jurnal Teknologi Laboratorium)
Burdock root (Arctium lappa L.) is a good plant for wound healing because it contains lignans, flavonoids, and phenolic acid which have the potential as anti-inflammatory, anti-allergic, anti-cancer, free radical scavengers and antioxidants. This research aims to determine the effectiveness of burdock root extract (Arctium lappa L.) on wound healing in white rats (Rattus norvegicus). The research design of laboratory experiments, with animal samples Rattus norvegicus, were grouped into five groups: three treatment groups with burdock root extract concentrations of 15%, 30%, and 45% and two control groups such positive control with povidone iodine and negative control with basic gel. The results showed that burdock root extract (Arctium lappa L.) concentrations of 30% and 45% had significant differences between the positive and negative control groups in the wound healing process. Burdock root extract (Arctium lappa L.) with a concentration of 45% has the best effectiveness compared to a concentration of 30% or 15% in the healing process of cuts in white rats (Rattus norvegicus).